A Dual-Microcontroller IoT Platform for Integrated Flood and Air Quality Monitoring: Performance and Integration Challenges - Rafiuddin Syam; Baso Maruddani; Eko Kuncoro Pramono; Irma Ratna Kartika; Daffa Ihsanullah Irsyad (Malikussaleh University, Aceh, Indonesia, 2025)
Jakarta faces escalating environmental challenges, including heightened flood risk and deteriorating air quality, driven by rising rainfall intensity and increasing pollution levels. Conventional monitoring systems for these hazards often operate in isolation, lacking the integration, realtime capability, and accessibility offered by modern Internet of Things (IoT) technology. To address this gap, this study designed and developed a unified, dual-microcontroller IoT platform for the simultaneous and integrated monitoring of flood potential and air pollution. The research followed an Experimental Development methodology, involving systematic hardware design, firmware development, system integration, and rigorous performance testing. The prototype hardware architecture strategically separates data acquisition and network communication by utilizing an Arduino Uno for data acquisition and an ESP32 microcontroller for network communication, respectively. The system incorporates an HC-SR04 ultrasonic sensor for water level detection, a DHT22 sensor for temperature and humidity measurement, and an MQ-135 gas sensor for assessing air quality. Data is displayed locally on a 20×4 LCD and transmitted to a cloud server. A critical finding from the integration phase was a 2.3% data loss rate attributable to serial communication instability between the microcontrollers, highlighting a significant challenge in multi-processor IoT architectures and underscoring the necessity for robust inter-processor protocols. During a comprehensive 24-hour endurance test with measurements taken at ten-minute intervals, the system demonstrated high accuracy in individual sensor readings. It successfully transmitted 97.7% of the data in realtime to a web application built on the Firebase platform. The study concludes that while the integrated dual-microcontroller approach is highly viable for holistic environmental monitoring, future iterations must prioritize enhanced communication reliability through hardware flow control and error-checking mechanisms to achieve the robustness required for mission-critical deployments.